Pas de talents à perdre : priorité à l’alphabétisation (2008)

Conference Announcement and Call for Presentations - Quebec Association for Adult Learning (QAAL) (2008)

Recognition awards for adult literacy : Submissions - Quebec Association for Adult Learning (QAAL) (2008)

Adult ESL and Literacy : Issues and Options - Spruck Wigley, Heide (The Centre for Literacy of Quebec (CFL), 2008)
In this paper, I would like to put forward a number of issues for us to think about and discuss. At the same time, I argue for a better articulated system that more closely matches the needs and goals of various subgroups of English language learners.